2008
DOI: 10.1529/biophysj.107.114637
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Transferrin-Receptor Interactions at the Single-Molecule Level

Abstract: Interaction between the iron transporter protein transferrin (Tf) and its receptor at the cell surface is fundamental for most living organisms. Tf receptor (TfR) binds iron-loaded Tf (holo-Tf) and transports it to endosomes, where acidic pH favors iron release. Iron-free Tf (apo-Tf) is then brought back to the cell surface and dissociates from TfR. Here we investigated the Tf-TfR interaction at the single-molecule level under different conditions encountered during the Tf cycle. An atomic force microscope tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 55 publications
5
38
0
4
Order By: Relevance
“…The results of earlier cell binding assays suggested that iron removal from hTf results in a dramatic reduction of its receptor affinity (6)(7)(8)(9), while the results of more recent biophysical studies were consistent with a complete loss of the receptorbinding competence for the apo-hTf under conditions mimicking the extra cellular environment (11)(12)(13)(14). ESI MS provides conclusive evidence that aTf has the ability to form relatively stable complexes with TfR at neutral and mildly basic pH.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of earlier cell binding assays suggested that iron removal from hTf results in a dramatic reduction of its receptor affinity (6)(7)(8)(9), while the results of more recent biophysical studies were consistent with a complete loss of the receptorbinding competence for the apo-hTf under conditions mimicking the extra cellular environment (11)(12)(13)(14). ESI MS provides conclusive evidence that aTf has the ability to form relatively stable complexes with TfR at neutral and mildly basic pH.…”
Section: Discussionmentioning
confidence: 87%
“…However, other studies failed to detect apo-hTf binding to TfR at neutral pH (10), and similar conclusions came from work specifically targeting the hTf/TfR interaction using orthogonal biophysical techniques, such as surface plasmon resonance-based binding assays (11)(12)(13) and atomic force microscopy (14). As a result, the idea of apo-hTf/TfR association at neutral pH became increasingly apocryphal.…”
Section: Metalloprotein | Protein Interactionmentioning
confidence: 85%
“…Besides the capability of high resolution topographic imaging, a singular advantage of AFM is the ability of identifying protein species via specific interactions. This principle has been adapted in studies of biomimic surfaces and living cells [10][11][12][13][14]. Here we apply this method in revealing the distribution and association of TRA-1-81 on undifferentiated and differentiated hES cells at the single cell level.…”
Section: Introductionmentioning
confidence: 99%
“…La proteína puede almacenar hastaneuroferritinemia con un fenotipo de sobrecarga de hierro en el cerebro, igualmente se puede presentar como hiperferritinemia y las cataratas son la principal complicación (42,43). (45,46). Es considerado el principal captador celular de hierro y se localiza en la membrana del enterocito, del hepatocito, de los eritrocitos, en la placenta, en la médula ósea y en el músculo esquelético (9,11,33,47,48).…”
Section: El Transportador 1 De Metales Divalentes (Dmt1)unclassified